Exploring gender disparities in public health education: a gender-disaggregated analysis of selected public sector institutions in Pakistan - Masood Ali Shaikh; Syed Muhammad Mubeen (Journal of the Pakistan Medical Association, 2026)
There is a dearth of gender disaggregated analysis of faculty at public sector institutes and schools of public health in Pakistan. A web-based search was conducted to identify public health institutes in the public-sector, offering postgraduate education with faculty names on their websites. Four institutions were identified: APPNA Institute of Public Health at Jinnah Sindh Medical University in Karachi, Health Services Academy in Islamabad, Institute of Public Health in Lahore, and the School of Public Health at Dow University of Health Sciences in Karachi. Faculty data, including gender and academic titles, were extracted from the official websites between April 19 and 20, 2025. Cumulatively, data was analysed for 100 full-time teaching faculty members, which revealed that women were predominantly represented in junior and mid-level roles, while senior academic ranks were largely held by men. Findings highlight the need for focussed policy action to address gender disparities among the faculty imparting public health education in Pakistan. Key words: Women, Faculty, Schools, Public health, Pakistan.